2022
DOI: 10.3390/cryst12060805
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hot Isostatic Pressing in Nickel-Based Single Crystal Superalloys

Abstract: Hot isostatic pressing (HIP) technology can effectively reduce microstructure defects such as micropores, which are formed during solidification and hominization heat treatment, and thus further improve the high temperature performance of nickel-based SX superalloys. This paper reviews the application of HIP treatment in nickel-based SX superalloys, focusing on the dislocation-creep closure and diffusion-creep closure mechanisms and the kinetics of annihilation of micropores by HIP. The effects of different sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Thus, research on the structural stability and high-temperature stress rupture property of the DD6 under actual service conditions is very important. Zhao Y. et al studied the effects of thermal isostatic pressing on the microstructure defects, and of the stress rupture property on the second-generation solid-solution single-crystal superalloy, and clarified the mechanism of how thermal isostatic pressing improved the structural state and the stress rupture property of the Ni-based alloy under different initial structural states [20]. Lv et al studied the microstructure and creep properties of two low-cost single crystal superalloys under different creep conditions and found that the high-Re-alloy γ phase microstructure had better stability and a smaller deformation degree at high temperatures [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, research on the structural stability and high-temperature stress rupture property of the DD6 under actual service conditions is very important. Zhao Y. et al studied the effects of thermal isostatic pressing on the microstructure defects, and of the stress rupture property on the second-generation solid-solution single-crystal superalloy, and clarified the mechanism of how thermal isostatic pressing improved the structural state and the stress rupture property of the Ni-based alloy under different initial structural states [20]. Lv et al studied the microstructure and creep properties of two low-cost single crystal superalloys under different creep conditions and found that the high-Re-alloy γ phase microstructure had better stability and a smaller deformation degree at high temperatures [21].…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что заготовки и готовые изделия, полученные методом ГИП, обладают повышенной усталостной прoчнoстью, высоким сопротивлением коррозии, а также увеличенным ресурсом работы [11].…”
unclassified